2012
DOI: 10.1089/end.2012.0258
|View full text |Cite
|
Sign up to set email alerts
|

Role of Active Mentoring During Flexible Ureteroscopy Training

Abstract: Mentorship during flexible ureteroscopy training results in higher GRS and lower TCT at the end of the training. Self-assessment GRS by trainee does not correlate well with the skills acquired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Flexible ureteroscopy (fURS) is increasingly used as a first‐line treatment and it is not surprising that in some countries it exceeds all other modalities by up to 30% . fURS has become popular with urologists, as it is easy to learn, is associated with high stone‐free rates, and is acceptable to patients .…”
Section: Introductionmentioning
confidence: 99%
“…Flexible ureteroscopy (fURS) is increasingly used as a first‐line treatment and it is not surprising that in some countries it exceeds all other modalities by up to 30% . fURS has become popular with urologists, as it is easy to learn, is associated with high stone‐free rates, and is acceptable to patients .…”
Section: Introductionmentioning
confidence: 99%
“…While RIRS needs a structured training program with virtual reality or high fidelity non-virtual reality models, microperc can be more easily mastered by any Urologist who is trained in standard PCNL. [2324]…”
Section: Introductionmentioning
confidence: 99%
“…Their effect on the outcome was assessed by a global rating scale (GRS), the task completion time (TCT) and the learning curve. Validation studies were found in 14 articles ( Table 2 ) [7–32] .…”
Section: Resultsmentioning
confidence: 99%
“…Randomised controlled trials (RCTs) were reported in four articles [10,14,21,33] . Matsumoto et al [10] investigated the effect of bench-model fidelity, whereas Wilhelm et al [14] and Watterson et al [33] investigated the acquisition of skills using a computer-based VR endourological simulator.…”
Section: Validation Studiesmentioning
confidence: 99%